2017
DOI: 10.1177/0194599817696502
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation in Inner Ear Malformations: Systematic Review of Speech Perception Outcomes and Intraoperative Findings

Abstract: Objective (1) To analyze reported speech perception outcomes in patients with inner ear malformations who undergo cochlear implantation, (2) to review the surgical complications and findings, and (3) to compare the 2 classification systems of Jackler and Sennaroglu. Data Sources PubMed, Scopus (including Embase), Medline, and CINAHL Plus. Review Methods Fifty-nine articles were included that contained speech perception and/or intraoperative data. Cases were differentiated depending on whether the Jackler or Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 72 publications
(163 reference statements)
3
46
0
8
Order By: Relevance
“…In a recent meta-analysis, Farhood et al [2017] found IEM to be associated with a high rate of gusher (39.1%) and FN anomalies (34.4%). Confronted with an aberrant morphology, an intricate electrode insertion, a high risk of developing postoperative CSF leak/meningitis, and an inconsistent FN course, many groups advocate the use of STP for secure CI [Colletti et al, 1998;Free et al, 2013;Szymański et al, 2016].…”
Section: Inner-ear Malformationsmentioning
confidence: 99%
“…In a recent meta-analysis, Farhood et al [2017] found IEM to be associated with a high rate of gusher (39.1%) and FN anomalies (34.4%). Confronted with an aberrant morphology, an intricate electrode insertion, a high risk of developing postoperative CSF leak/meningitis, and an inconsistent FN course, many groups advocate the use of STP for secure CI [Colletti et al, 1998;Free et al, 2013;Szymański et al, 2016].…”
Section: Inner-ear Malformationsmentioning
confidence: 99%
“…Thus, various methods such as ABR, the 40 Hz-related potential, and behavioral audiometry have failed in measuring residual hearing before implantation [7][8][9]. Before the operation, determining the residual hearing of patients and accordingly evaluating the function of the auditory nerve are important means to judge the curative effect of the cochlear surgery.…”
Section: Discussionmentioning
confidence: 99%
“…in Referiert + Diskutiert starten wir mit einer wegweisenden Arbeit aus dem New England Journal of Medicine, dass es bei einer Antibiotikatherapie der kindlichen Otitis media acuta wichtig ist auch konsequent über 10 Tage zu behandeln [1]; eine Kurzzeittherapie ist dem eindeutig unterlegen. Dann geht es um die Effektivität von Dehnungsimplantaten bei Septorhinoplastiken und dann um radiologische Befundung von Fazialisanomalien bei Innenohranomalien, was auch für CI Implantationen relevant ist, siehe weiter unten [2].…”
Section: Liebe Leserinnen Und Leserunclassified